2022
DOI: 10.1038/s41419-022-04669-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced long noncoding RNA NR2F1-AS1 maintains pancreatic cancer proliferation, migration, and invasion by activating the NR2F1/AKT/mTOR axis

Abstract: Accumulating evidence has demonstrated the essential role of long noncoding RNAs (lncRNAs) in various types of human cancer, including pancreatic cancer (PC). However, the functions and regulatory mechanisms of nuclear receptor subfamily 2 group F member 1 antisense RNA 1 (NR2F1-AS1) that are responsible for its role in the malignant progression of PC cells remains to be investigated. In this study, the biological effects of NR2F1-AS1 and NR2F1 in PC were investigated by in vitro and in vivo experiments. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In addition, functional experiments demonstrated that NR2F1-AS1 upregulation repressed CC cell proliferation, migration, invasion, and EMT process. These findings demonstrated that NR2F1-AS1 acted as a tumor suppressor in CC, which is inconsistent with the general oncogenic role of NR2F1-AS1 in multiple other cancers, such as neuroblastoma34, gastric cancer35, and pancreatic cancer 36 .…”
Section: Discussionmentioning
confidence: 87%
“…In addition, functional experiments demonstrated that NR2F1-AS1 upregulation repressed CC cell proliferation, migration, invasion, and EMT process. These findings demonstrated that NR2F1-AS1 acted as a tumor suppressor in CC, which is inconsistent with the general oncogenic role of NR2F1-AS1 in multiple other cancers, such as neuroblastoma34, gastric cancer35, and pancreatic cancer 36 .…”
Section: Discussionmentioning
confidence: 87%
“…Numerous studies have revealed that dysregulated lncRNA participates in processes of carcinogenesis and progression of pancreatic cancer. For instance, Liu has reported that lncRNA NR2F1-AS1 promotes proliferation and invasion of pancreatic cancer by regulating the neighboring NR2F1 gene and activating AKT/mTOR signaling pathway ( Liu et al, 2022 ). Huang has demonstrated that lncRNA LNC00842 prompts the malignancy of pancreatic cancer by preventing acetylate PGC-1α from deacetylation and remodeling the metabolic status of cancer cells ( Huang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The active AKT/mTOR pathway promotes PC cell proliferation, migration, and invasion. Moreover, it was suggested that NR2F1-AS1 may be a potential prognostic biomarker and therapeutic target for PC [ 40 ].…”
Section: Lncrnas In Pancreas Cancermentioning
confidence: 99%